Management of delirium in a medical and surgical intensive care unit. (5th December 2020) - Shivji, Sheliza; Stabler, Sarah N.; Boyce, Krystin; Haljan, Gregory J.; McGloin, Rumi
Abstract: What is known and objective: Delirium has been associated with increased mortality and prolonged hospital length of stay among critical care patients. Furthermore, treatment of delirium remains variable amongst clinicians due to limited evidence. The objective of this study was to determine the local incidence of delirium and to characterize the effectiveness and safety of pharmacological therapy used to treat delirium. Methods: A retrospective chart review evaluated patients diagnosed with delirium (Intensive Care Delirium Screening Checklist score ≥4) and requiring mechanical ventilation for ≥48 hours from January 2016 to June 2017. The primary outcomes included comparison of resolution, the time to first resolution and recurrence of delirium in patients prescribed pharmacological and/or pre‐emptive therapy versus those who did not. Secondary outcomes included incidence of adverse effects of drug therapy and delirium attributable adverse events. Results and discussion: The incidence of delirium during our defined study period was 49%. Of the 178 patients included in the study, 136 (76%) received drug therapy for delirium. Agents used for treatment of delirium included dexmedetomidine ( n  = 90 [66%]), haloperidol ( n  = 77 [57%]), and quetiapine ( n  = 74 [54%]). Resolution of delirium occurred in 94 (52%) of patients and the difference was statistically significant favoring patients who did not receive pharmacological therapy. There was no difference in the median time to resolution of delirium (3 days) for patients who received pharmacological and/or pre‐emptive therapy versus those who did not. Bradycardia and hypotension were the most frequently documented medication‐related adverse events. Self‐removal of an invasive line/catheter, was reported in 36 (26%) patients despite receiving pharmacological treatment. What is new and conclusion: Despite unclear evidence that pharmacological interventions help with delirium management, the majority of our patients received such interventions. To improve patient outcomes, we should shift focus towards non‐pharmacological interventions for delirium. Abstract : Despite unclear evidence that pharmacological interventions help with delirium management, the majority of patients continue to receive such interventions. To improve patient outcomes, we should shift focus towards non‐pharmacological interventions for delirium.